Untreated morbidity and treatment-seeking behaviour among the elderly in India: Analysis based on National Sample Survey 2004 and 2014 - Shobhit Srivastava; Anayat Gill (Elsevier, 2020)
The changing demographic structure in India and worldwide accompanies with it a gamut of problems and opportunities. According to the Census of India, the proportion of elderly in the overall population rose from 5.6 per cent in 1961 to 8.6 per cent in 2011 and is expected to rise to 20 per cent in 2050. Considering the consequent growing challenges in healthcare the main aim of the study is to find essential determinants contributing to untreated morbidity among the elderly. Also, the paper examines treatment-seeking behaviour for infectious and chronic diseases among the elderly in India. Data from the 60th and 71st round of National Sample Survey Organization was used for the analysis. Relative differences were calculated along with logistic regression to study the objectives and the heckprobit model was used to carve out the treatment-seeking behaviour among the elderly in India. It was found that the overall decrease in relative decadal difference was 41% for untreated morbidity. In both the rounds, the elderly living below the poverty line had 42% and 50% more likelihood of untreated morbidities respectively in comparison to elderly not living below the poverty line. The study indicates that elderly who were living with a spouse in comparison to those living alone had less likelihood to have untreated morbidities. Also, elderly from rural areas and having lower levels of education had higher likelihood of untreated morbidity. Similar inequalities were observed in treatment-seeking behaviour as well, where it was found that elderly belonging to lower socio-economic status were less likely to seek treatment. Linking the results from the heckprobit model this study provides the evidence that social and economic factors play a significant role in affecting both untreated morbidity and treatment-seeking behaviour of elderly in India.